Roundtable Report: Taking the Agenda Forward: The Roundtable on Separated Children Seeking Asylum in Canada - Kumin, Judith; Chaikel, Danya (Refuge: Canada's Journal on Refugees, 2002)
On October 15 and 16, 2001, the National Roundtable on Separated Children Seeking Asylum in Canada was held in Ottawa. The meeting was organized by the Child Welfare League of Canada, International Social Service Canada, and the United Nations High Commissioner for Refugees (UNHCR) Branch Office in Canada. The organizers brought together immigration officials, child welfare professionals, and refugee advocates, in an effort to build partnerships and improve awareness of the problem of separated children seeking asylum in Canada. Participants discussed ways to resolve the tension between immigration and child protection concerns, as well as how to develop a consistent approach to the issue across Canada. Senator Landon Pearson generously agreed to host the event.